THE STUDENTS' PERCEPTION TOWARD THE IMPLEMENTATION OF ONLINE LEARNING IN ENGLISH EDUCATION DEPARTMENT OF UNIVERSITY OF ISLAM MALANG - rhizma nur fitria (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
ABSTRACT Fitria, N. R. 2021. The Students' Perception toward the Implementation of Online Learning in English Education Department of University of Islam Malang. Skripsi. English Education Department Faculty of Teacher Training and Education University of Islam Malang. Advisors 1) Muhammad Yunus, S.Pd., M.Pd. 2) Fitri Awaliyatush Sholihah, S.Pd., M.Pd. Key Terms: Perception; Online Learning. Online learning has widely applied in the field of education. It is claimed that online learning is effective. However, the students’ perception toward its implementation is not measured yet. On the implementation of teaching mode, the students also needs to be considered since student is one of the important components in the learning process. This study aimed to identify the students’ perception toward the implementation of online learning in learning English as well its advantage and challenge. The result will give an important consideration for the educational field to develop the implementation of online learning.The study employed descriptive qualitative design. The participants involved in this study were the students’ of English education department University of Islam Malang. There were five classes of this intake with a total number of 168 students. Those classes were 2018A, 2018B, 2018C, 2018D and 2018E. However, the researcher took 6 students of each class as the subject of the study. Two instruments were used in this study which included: questionnaire and interview. The parameter was adopted from Kalpana (2010) by considering on three aspects which include: student's usage of internet and knowledge of online learning, student's perception on benefits of online learning, and the challenge of online learning. The process of data analysis included data condensation, data display, and conclusion drawing and verification. The data gathered were then verified by an expert validator.The result of this study indicated that the students have low perception about online learning. It is because online learning gave the students some obstacles in the learning process. Those obstacles were such as: facilities, internet access, and the online learning itself. There was no clear guidance provided in online learning. These findings suggest that the implementation of online learning at English education department University of Islam Malang needed to be considered and developed.